Study on Hair Follicle Electromagnetism as Proposed Mechanism for the Presence of Bipolar Electrical Charges Inherent in the Human Hair Shaft - Sorondo, Abrahám Embí (Innovations in Science and Technology Vol. 7, 2022)
Human hair is made up of a follicle embedded in the skin and a projecting shaft. It has been described as a miniorgan with its own cell divisions, metabolism, and ageing stages, finally shedding old hair and regrowing new hair from the same follicular tissue. The magnetic field created by direct current (DC) in human hair follicles was found and introduced in 1980 using advanced magnetometers. Most recently in 2015, a tabletop optical microscopy method was developed and published in 2016, thus allowing for the detection of hair follicles and shaft biolectromagnetic fields. The rejection of several exogenous materials, such as a hair follicle, keratin flakes and small iron filings amongst others by a fresh human blood smear had also been described . Qualitative images are presented where the bipolar electrical property of the shaft is documented. This finding was inferred since blood tissue carries a negative charge, thus repelled by an equal charge; experiments support a positive (+) field as triggering coagulation. The shaft is repeatedly shown in experiments to express a contralateral positive side inducing clots. Fibrin formation is also documented by images showing intricate networks indicative of blood coagulation. In conclusion, the genesis of hair shafts bipolarity is shown resulting from a “gap” in the follicle biolectromagnetic fields inhibiting energy from fully engulfing the shaft.